The formation of tourists' behavioral intention in City Walk in Malaysia through the embodiment perspective - Zhenbin, Wang; Hui, Zhang; Chaoyi, Cao; Ramachandran, Sridar; Iqbal, Aatif (Elsevier B.V., 2025)
This study aims to investigate the formation of tourists' behavioral intentions in the context of City Walk experiences in Malaysia from an embodiment perspective. Guided by Cognitive Appraisal Theory, a quantitative research design was employed using Partial Least Squares Structural Equation Modeling (PLS-SEM). A total of 408 Chinese tourists were selected through purposive sampling and participated via both face-to-face and online surveys, given that China remains Malaysia's largest and continuously growing source of international tourists. The findings reveal that embodied cognition—operationalized through sensory experience, visitor engagement, and authenticity—along with the emotional response of memorable tourism experiences (MTEs), exerts a significant positive influence on behavioral intention. However, no substantial mediating effect was found for MTEs in the relationship between visitor engagement and behavioral intention in the City Walk context. This study contributes a novel conceptual framework grounded in contemporary cognitive theory, offering both theoretical advancements and practical implications for understanding emerging travel trends and promoting the sustainable development of urban tourism in Malaysia.